New Insights Into Cinnamoyl Esterase Activity of Oenococcus oeni - Collombel, Ingrid; Melkonian, Chrats; Molenaar, Douwe; Campos, Francisco M.; Hogg, Tim (Frontiers in Microbiology, 2019)
Some strains of Oenococcus oeni possess cinnamoyl esterase activity that can be relevant in the malolactic stage of wine production by liberating hydroxycinnamic acids that are precursors of volatile phenol compounds responsible for sensory faults in wine. The objective of this study was to better understand the basis of the differential activity between strains. After screening, five commercial strains of O. oeni were selected. Three of the strains were found to exhibit cinnamoyl esterase activity (CE+) and two not (CE-). Unlike its free form, the tartrate ester trans-caftaric acid was not toxic toward O. oeni. Although the usage of functional annotation of genes revealed genotypic variations between the strains, no specific genes common only to the three CE+ strains could explain the different activity. Pasteurized wine was used as a source of tartrate esters in growth and metabolism experiments conducted in MRS medium, whilst commercial trans-caftaric acid was used as available substrate for enzyme assay. In the case of the two CE+ strains OenosTM and CiNeTM, wine-exposed samples showed a more rapid degradation of trans-caftaric acid than the unexposed ones. The CE activity was present in all cell-free extracts of both wine-exposed and unexposed strains, except in the cell-free extracts of the CE- strain CH11TM. This activity may be constitutive rather than induced by exposure to the tartrate esters. Trans-caftaric acid was totally degraded into trans-caffeic acid by the cell-free extracts of the three CE+ strains, whilst cell-free extracts of the CE- strain CH16TM showed significantly lower activity, although higher for the strains in experiments with no prior wine exposure. Only in the case of the CE+ strains exposed to wine did the cell debris contain higher protein concentrations that the unexposed ones. Further bioinformatics synteny analysis of commonly found EstB28 esterase gene did not reveal any difference on the upstream regulation and transport functionality between the strains. This study highlights the complexity of the activity in the wine related O. oeni population. Variable cinnamoyl esterases or / and membrane transport proteins in the O. oeni strains analyzed and a possible implication of wine molecules could explain this phenomenon.